The Importance of the Forest Products Industry in the Wisconsin Economy - OYEKOLA AMOSUN, Olalere (University of Wisconsin-Stevens Point, College of Natural Resources, 1980)
The aggregated forest products industry is comprised of lumber and wood products, furniture and fixtures and paper and allied products industries. The contribution of the forest products industry in the Wisconsin economy from 1967 to 1977 was examined in terms of employment, payroll, value added, value of shipments, new capital expenditures, costs of materials, number of production workers and wages paid, using data from 1971 Census of Manufactures. The forest products industry ranked first among the Wisconsin manufacturing industries in investment on machinery; second in employment, payroll, value added, number of production workers and wage paid; third in value of shipments and fourth in costs of materials used. The industry will continue to experience moderate real growth in the next ten years 1978-1987. The most significant growth will take place in new capital expenditures and costs of materials. Data for payroll, value added, value of shipments, new capital expenditures, costs of materials and wages paid production workers were adjusted for inflation using 1967 as the base year.